2021
DOI: 10.1371/journal.pone.0245904
|View full text |Cite
|
Sign up to set email alerts
|

The predictive capacity of GARCH-type models in measuring the volatility of crypto and world currencies

Abstract: This paper provides a thorough overview and further clarification surrounding the volatility behavior of the major six cryptocurrencies (Bitcoin, Ripple, Litecoin, Monero, Dash and Dogecoin) with respect to world currencies (Euro, British Pound, Canadian Dollar, Australian Dollar, Swiss Franc and the Japanese Yen), the relative performance of diverse GARCH-type specifications namely the SGARCH, IGARCH (1,1), EGARCH (1,1), GJR-GARCH (1,1), APARCH (1,1), TGARCH (1,1) and CGARCH (1,1), and the forecasting perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
4
19
1
1
Order By: Relevance
“…This result confirms the findings from Naimy et al (2021), who showed that the most stable cryptocurrency is ten times more volatile than the most unstable fiat currency.…”
Section: Market Risk and Policy Implicationssupporting
confidence: 91%
“…This result confirms the findings from Naimy et al (2021), who showed that the most stable cryptocurrency is ten times more volatile than the most unstable fiat currency.…”
Section: Market Risk and Policy Implicationssupporting
confidence: 91%
“…Mostly, the flourishing interest of academia in this relatively new asset class was driven by its unique nature (see [ 2 , 3 ] for a comprehensive review). To all appearances, among the empirically documented inherent features of these synthetic currencies, it seems that so far several are indisputable, to wit, high volatility [ 4 6 ], clustering and long memory of volatility [ 7 10 ], the presence of jumps [ 11 13 ], high correlation within the crypto market [ 14 16 ] but relative isolation from other asset classes in normal times [ 17 19 ] and increased contagion in severe turbulent times [ 20 22 ], etc. The most disputable characteristics of this atypical asset refer to the investment or currency potential and its ability to act or not as a safe haven.…”
Section: Introductionmentioning
confidence: 99%
“…Sadik et al (2019) presented the NA-GARCH model for forecasting the stock price volatility, which is the combination of the GARCH model by examining the effects of quantified news sentiment on the movement of stock prices. Finally, Naimy et al (2021) compared the accuracy of GARCH models in assessing the cryptocurrencies volatility. Many financial time series data show a nonlinear dependency structure, but in GARCH models, a linear correlation structure is generally assumed between time-series data; hence, these models do not usually record the nonlinear patterns.…”
Section: Classical Modelsmentioning
confidence: 99%